Customer Perceptions of Service Quality in the Banking Sector - Leninkumar, Vithya (Archives of Business Research, 2019)
Service quality is a powerful weapon which is used by the marketers to differentiate their services from the competitors. In this context, this study investigates the difference between the banks in respect to the service quality dimension. SERVQUAL model has been selected to measure the service quality in Northern Province of Sri Lanka. Four main commercial banks were selected for the study. Three hundred and fifty questionnaires were issued for data collection based on Convenience sampling method. SPSS version 18 was used for data analysis. Discrepancy was found in customer perception of services in terms of tangibles and reliability dimensions between banks.